Religious Autonomy and the Existential Process of Agency: A Comparative Analysis of the Foundations of Women’s Moral Agency in Kant’s Philosophy and Shi’i Islam - Shiravand, Mohsen (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2026)
This study conducts a comparative analysis of women’s moral agency within two intellectual frameworks: Kant’s practical philosophy and Shi’i Islam. The central research question is: How is the structure of women’s moral agency formulated in these systems, and how does each address the gap between inner subjectivity and the external actualization of agency? In the Kantian section, employing conceptual analysis, the contradiction between the transcendental autonomous subject and the empirical subject of woman characterized by deficient rationality is analyzed as the primary obstacle to the objective realization of women’s agency. In the Shi’i Islamic section, drawing on Quranic foundations such as fiṭrah (primordial nature) and khilāfah (vicegerency), and mediated by the views of Mullā Ṣadrā on substantial motion, Ṭabāṭabāʾī on credal perceptions, and Muṭahharī on psycho-emotional differences, a model of “situated agency” is presented. In this model, women’s psycho-physical differences are regarded not as deficiencies, but as existential gradations and a basis for the wise distribution of responsibilities. The legal institutions of Shi’i Islam, including mahr, nafaqah, and independent property rights, function as structural supports for agency, facilitating the transition from inner subjectivity to external actualization. The novelty of this research lies in its formulation of “religious autonomy” in contrast to Kantian autonomy.